Oxygen Saturation Targeting During Delivery Room Stabilization: What Does This Mean for Regional Cerebral Oxygenation? - Binder-Heschl, Corinna; Pichler, Gerhard; Avian, Alexander; Schwaberger, Bernhard; Baik-Schneditz, Nariae; Mileder, Lukas; Heschl, Stefan; Urlesberger, Berndt (Frontiers in Pediatrics, 2019)
Objective: To investigate if preterm neonates with arterial oxygen saturation (SpO2) <80% at 5 minutes after birth show different regional cerebral tissue oxygen saturation (rcStO2), compared to infants reaching the target. Methods: Retrospective analysis of four prospective observational studies. Preterm neonates needing respiratory support during delivery room stabilization were included. Regional cerebral tissue oxygen saturation was measured with near-infrared spectroscopy during the first 15 minutes after birth along with SpO2 and heart rate (HR). Neonates were divided into two groups: those with a 5-minute SpO2 ≥80% (“≥80% group”) and those with a 5-minute SpO2 <80% (“<80% group”). Groups were compared regarding rcStO2, SpO2 and HR. Furthermore, we analyzed whether a 5-minute SpO2 <80% was associated with a rcStO2 below the 10th percentile at the same time point. Results: 146 neonates were included, with 68 (47%) in the “≥80% group” and 78 (53%) in the “<80% group”. Neonates in the “<80% group” had a significantly lower rcStO2 (p< 0.001). Furthermore, 80.3% of neonates in the “<80% group” and 23.4% in the “≥80% group” had rcStO2 values below the 10th percentile at 5 minutes (p<0.001). HR was significantly lower at minute 3 and 4 in the “<80% group” (p<0.002). Conclusion: Preterm infants needing respiratory support, who do not reach the SpO2 target of 80% at 5 minutes after birth, show significantly diminished rcStO2 values compared to neonates reaching the target.